Estimation of the Dietary Calcium and Nonphytate Phosphorus Needs of Growing Commercial Tom Turkeys Weighing Four to Twelve Kilograms - Roberson, Kevin D. (International Journal of Poultry Science, 2004)
An experiment was conducted to evaluate the dietary calcium and phosphorus needs of commercial toms during the grower feeding period of 8 to 14 wk of age. Dietary calcium and nonphytate phosphorus were formulated to be fed at 60, 75, 90, 105 or 120% of the NRC (1994) requirements based upon three-wk phase feeding periods. A corn-soybean meal based diet was fed in mash form to Large White turkeys that had been fed adequate calcium and nonphytate phosphorus for 8 wk and weighed an average of 4.44 kg at the start of the experiment. Growth was improved linearly from 8 to 11 wk of age and for the entire experiment by increasing amounts of dietary calcium and nonphytate phosphorus. Bone strength, as measured by fracture force, was increased linearly at 11 and 14 wk of age by increasing levels of dietary calcium and nonphytate phosphorus. Based upon analyzed nutrient values and feed disappearance, it was estimated that growing toms need approximately 2 g of nonphytate phosphorus per day during the growing period when a calcium:nonphytate phosphorus ratio of approximately 2:1 is fed and the toms are gaining about 180 g/d.